Data Security in Social Assistance Applications Using the AES-128 Algorithm - Dani Yusuf (LPPM Universitas Islam 45 Bekasi, 2025)
Social assistance is one of the government's programs aimed at helping people in need. However, the process of applying for social assistance often faces issues related to data security, particularly the personal data of aid recipients. This research aims to implement the Advanced Encryption Standard (AES) algorithm with a 128-bit key (AES-128) in the social assistance application system to enhance data security. The system development method used is the prototype approach, which allows for iterative and participatory system development. The results show that the implementation of AES-128 can effectively secure sensitive data, such as identification numbers, addresses, and financial information. This system is expected to be a solution for increasing public trust in the social assistance application process.